Pengaruh Promosi dan Brand Ambassador terhadap Keputusan Pembelian Konsumen Tokopedia : (Studi pada Mahasiswa Institut Teknologi dan Bisnis Semarang Kampus II) - Devi Enisa; Riyono Riyono; Hesti Ristanto (Jurnal Bingkai Ekonomi (JBE), 2024)
The research entitled "The Influence of Promotions and Brand Ambassadors on Purchasing Decisions among Tokopedia Consumers" is the result of quantitative research. This research aims to answer the question about how promotions and brand ambassadors influence purchasing decisions among Tokopedia consumers. The research methodology used is quantitative research using survey methods. The sampling technique used purposive sampling with a total of 81 respondents. The data collection technique uses a questionnaire processed using SPSS version 22. Data analysis uses multiple linear regression. The research results show that promotions have a partial effect on purchasing decisions for Tokopedia consumers, this is proven by a significance value of 0.028 <0.05. Brand ambassadors also partially influence purchasing decisions among Tokopedia consumers, this is proven by a significance value of 0.017 < 0.05.